Cow milk αs1-casein induces allergic responses in a mouse model of atopy - Guangyu Wang; Xiaofeng Yu; Yanjun Cong; Linfeng Li (Food Science and Human Wellness, 2022)
ABSTRACT: αs1-Casein is a potential allergen to induce hypersensitivity in cow milk. We had identified αs1-casein and its epitopes in previous studies. The present study aimed to evaluate the allergic mechanism of αs1-casein in a BALB/c mouse model. The levels of specific IgE, mast cell proteinase, histamine and cytokines in sensitized mice were determined, and the clinical and pathological observation were evaluated. Results showed that the levels of specific IgE, mast cell proteinase, histamine, IL-4, IL-5, IL-10 increased significantly with a dose-dependent trend. The local alveolar septum collapsed or thickened, and lymphatic foci were produced in the spleen and thymus, and the inflammatory cells infiltrated in small intestinal mucosa mesenchyme. In conclusion, the levels of specific IgE, mast cell proteinase, histamine, IL-4, IL-5, IL-10 and some inflammatory factors could possibly serve as allergic biomarkers of αs1-casein, however, additional studies on signal transduction and gene expression are necessary in future.